Assessment of structural condition of a historic masonry minaret in Egypt - Maher A. Adam (Case Studies in Construction Materials, 2020)
Egypt has many monumentality masonry minarets; most of them were constructed in the last two centuries 19th and 20th. Many of these minarets suffer from material aging, deterioration, adverse environmental conditions and lack of maintenance. Concerns regarding the safety limits of these heritage structures take place, and the necessity for structural assessment activities currently are going on and the need for proper analysis that will address the actual behavior of the minaret is required.This paper presents the condition assessment and structural analysis of a heritage masonry minaret (Al-Rifa’i minaret), that represents a typical example of these kind of structure in Egypt. Its current condition is studied including identification of the building materials, evaluation of the actual deteriorated material properties and estimation of the current loading conditions. A finite element model has been created using ANSYS v.15 program with its nonlinear capabilities, different loads have been considered such as the structure own weight, wind and seismic loads in accordance with the local codes, static and dynamic loads have been applied to determine the worst expected loading case in order to assess minaret structural efficiency, safety margin and serviceability limits. A comparison between static and dynamic analysis is performed, also linear and non-linear analysis have been compared and the obtained results regarding stresses, deformations and cracking within the structure indicates overall stability and safety of the structure in its current condition.